Servqual Model in Tourism Development in the Mandalika Special Economic Zone - Suci Arliani; Asfarony Hendra Nazwin; Mustamin Mustamin; Rifaid Rifaid; Theresia Octastefani (ARISTO, 2026)
The Mandalika Special Economic Zone (SEZ) is considered a very important tourism destination. However, its management faces problems such as the centralization of ITDC authority, limited community participation, and poor service quality in various areas.  In this situation, service quality evaluation must be carried out comprehensively using an approach that can see multi-actor dynamics.  The purpose of this study is to examine how the application of the SERVQUAL model helps improve tourism service quality in the Mandalika SEZ and to identify how ITDC, the Central Lombok Tourism Office, and Pokdarwis contribute to the five main dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The method used is a descriptive qualitative approach with in-depth interview and participatory observation techniques, thematic analysis assisted by NVivo 12 Plus.  The results show that ITDC authorities dominate the tangibles dimension through infrastructure development and area aesthetics, while trust, responsiveness, assurance, and empathy are more influenced by regional institutional capacity and community empowerment, including human resource training, provision of information centers, organization of cultural activities, and development of community-based ecotourism. The results show that physical development is not the only factor contributing to service quality improvement; institutional coordination, investment in human resources, and strengthening the role of the community are all factors that contribute to service quality improvement.  This study finds that SERVQUAL has the ability to explain the configuration of Mandalika's service governance and serves as the basis for a more inclusive and sustainable service improvement model in destinations with a multi-actor structure. Keywords: Servqual Model Service Quality; Mandalika SEZ; Sustainable Tourism; Community empowerment;